Exploring the Reality and Aspirations of Muslims: The divisions of the Umat in Indonesia - Kato, Hisanori (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2021)
Islam in Indonesia has played an important role in socio-political development in its recorded history. However, it is also true that there have been various theological and political debates and disagreements in the umat. The implementation of syari’at Islam is one of the major subjects of such discussions. The emergence of liberal movement in the post-Suharto era also brought about the difference of opinion among Muslims. In other words, the umat has never been united as a single entity in Indonesia. This “divided” umat faces several challenges in the present day in Indonesia. That includes terrorism committed by militant Muslims. In addition to the effort to prevent terrorism, it is equally important to de-radicalise perpetrators of such violent and barbaric acts. Despite some discrepancy in the umat, we see several attempts and cooperation of Muslims to make former terrorists reintegrated in the society. This paper shows how the re-radicalisation programme for former terrorist executed. The author also intends to examine the socio-political development of the umat in modern Indonesia with regard to subjects of syari’at Islam and liberal movement. Based on these examinations, sociological analysis on religion is also presented in the paper.